The aggressivness of Diaporthe longicolla and Diaporthe pseudolongicolla isolates tested by the soybean seed's artificial inoculation - Duvnjak, Tomislav; Sudarić, Aleksandra; Vrandečić, Karolina; Mijić, Anto; Čupić, Tihomir; Liović, Ivica; Matoša Kočar, Maja (2021)
This study"s objective was to determine if there was a difference in aggressiveness between the Diaporthe longicolla and the Diaporthe pseudolongicolla isolates infecting the soybean seeds. An artificial inoculation was performed under laboratory conditions and in a greenhouse on a soybean cultivar (Tisa) created in the breeding program of the Agricultural Institute Osijek and represented in a large-scale production in the Republic of Croatia. An attempt was made to discover whether the isolates of the recently described D. pseudolongicolla were more aggressive to the soybean seeds than the D. longicolla isolates, which have manifested a high aggressiveness to the soybean seeds throughout a series of earlier experiments. The D. pseudolongicolla isolates used in the experiment were isolated from the infected seeds pertaining to a wide production in the vicinity of Osijek.
Cilj ovoga rada bio je utvrditi postoje li razlike u agresivnosti između izolata fitopatogenih gljiva Diaporthe longicolla i Diaporthe pseudolongicolla koje zaražavaju sjeme soje. Obavljena je umjetna infekcija u laboratorijskim uvjetima i u plasteniku na kultivaru soje (Tisa) kreiranome u oplemenjivačkom programu Poljoprivrednoga instituta Osijek i zastupljenom u širokoj proizvodnji u Republici Hrvatskoj. Pokušalo se doći do odgovora jesu li izolati nedavno opisane D. pseudolongicolla, agresivniji za sjeme soje od izolata D. longicolla za koji se kroz seriju ranijih pokusa utvrdila visoka agresivnost na sjemenu soje. Pokus je postavljen na Poljoprivrednome institutu Osijek, a izolati D. pseudolongicolla korišteni u pokusu izolirani su sa zaraženoga sjemena iz široke proizvodnje u okolici Osijeka.
Bibliografija: 37 jed.
Summary ; Sažetak.
Keywords: Soja -- Sjeme -- Umjetna infekcija -- Patogenost -- Fitopatogene gljive